Influence of the breast prosthesis volume in dose distribution in radiotherapy planning - Fonseca, Paulo Victor; Salviano, Danilo; Ercolin, Laura; Buongosto, Fernanda; Borges, Allison; Marcelino, Francisco Américo Silveira; César, Dayane Lima; Silva, Rose Marta dos Santos; McCloskey, Susan Ann; Altei, Wanessa Fernanda; et al. (Mastology, 2021)
Introduction: The challenge of modern radiotherapy (RT) in breast cancer is to maintain its satisfactory oncological results, adapting to oncoplastic surgery and avoiding possible cosmetic damage. Considering that the breast prosthesis is not a target volume in RT planning, this study sought to analyze the effect of this volume on the coverage of the clinical target volume (CTV) of the breast. Methods: We performed a retrospective analysis of plans in 48 patients who submitted to RT in the first half of 2014. Two volumes were measured, such as breast CTV (breast tissue with the prosthesis) and real CTV (breast tissue excluding the prosthesis). The D95% values (dose that covers 95% of the volume) for each of them were verified and related to the volume of each one as well as the volume of breast prosthesis. Results: The analysis of the CTVs showed a significant difference between the mean volumes for the real CTV and breast CTV. While performing the CTV coverage, including the prosthesis, there is a perception that the dose covered 95% of the volume. Nevertheless, the analysis of the same plan after prosthesis volume exclusion revealed a difficulty in covering 95% of the breast tissue volume, indicating the interference of the prosthesis in therapy planning. Considering the dosimetric aspects, there were patients with real CTV values below the ideal dose of 47.5 Gy, after exclusion of implant volume.Conclusions: Our data reflected the volume of the prosthesis as an important variable that should be considered when planning adjuvant RT.